Influence of The Financial Performance of Islamic Business Units on The Benefit of Stakeholders - Raja Ria Yusnita; Eka Nuraini Rachmawati; Asdelina Ritonga (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Many studies are related to financial performance but only a few studies on the implementation of maslaha in Islamic banking, especially in Indonesia. This study aims to analyze the influence between financial performance and stakeholder benefits. This paper uses 20 Islamic Business Units in Indonesia with the period 2017 to 2021. The variables include financial performance (non-performing financing, return on assets, Operating Costs to Operating Income, Financing Funding Ratio) and Stakeholder Beneficence (Employees, Government, Community, Financing Consumers). This model is analyzed by linear regression with Partial Least Square (PLS) technique. The results show that financing performance affects the benefit of stakeholders, more specifically to the benefit of employees and the benefit of the community, and the government is the last party to benefit from the financial performance of UUS. This paper is a consideration for the government to pay more attention to policies that support the financial performance of UUS, so that, by providing appropriate support, the government can encourage the growth of UUS and in turn increase the benefits obtained by various parties, including the government itself.